Assessing the growth performance of European olive (Olea europea L.) on Mount Weld pastoral station - Price, Gary Norman (Curtin University, 2006)
This thesis describes the growth of European olive (Olea europaea L.) at three different trial sites located near Laverton, in the north-eastern Goldfields region of Western Australia. The local region comprises part ofthe rangelands area of Australia and has a semi-arid climate. The initial reason for planting olives was indirectly related to the rapid decrease in the local population and the economic downturn that resulted within that community during the late 1990's. This prompted an investigation into other possibilities for economic diversity for remote communities such as Laverton, which are located in the rangelands area of Australia. In Australia, much of the southern and eastern areas of the country have similar climate to traditional olive growing areas in Europe. [n the rangelands however, the environment is different to most other areas in the world where olive trees are grown and there is a notable absence of a commercial olive industry. Whilst locally, individual trees were also observed to be growing well and fruiting abundantly, it is not known whether it is possible to grow olive trees successfully on a commercial scale. Two preliminary trials were established in an ad-hoc manner, to examine whether olive trees could be grown successfully in the rangelands environment. Eighty-eight trees of 5 different cultivars were planted on a shallow, clay soil profile at the first trial site. Ninety-eight trees of 11 different cultivar were planted on a deep sand soil profile at the second site. Higher mortality rate occurred at the first site, with most tree deaths being recorded in the first two years. Peak growth of branch tips occurred during the spring-summer seasons at both sites. Differences in trial design and timing of planting prevented statistical comparison of growth performance between sites however.A third olive trial, consisting of 3 olive groves was established according to randomised design. In the north and middle groves, 54 trees of 3 different cultivar were planted on a deep alluvial soil profile. In the south grove, 53 trees of 3 different cultivar were planted on a shallow clay soil profile. High mortality rates were recorded at all 3 groves during the first year, as a result of high salinity levels in irrigation water during the establishment period. Overall, most tree mortality was recorded at the south grove. Significantly higher growth performance occurred within the deeper alluvial soil profile at the north and middle groves, compared to the shallow clay soil profile in the south grove. Negligible olive fruit production occurred at the first site. At the second site, small quantities of olive fruit were produced during some seasons only. No olive fruit production occurred at any grove at the randomized site. Successful fruit formation appears directly related to tree health, as a function of water supply. Ripening of olive fruit occurred earlier than at other more temperate olive growing areas of Australia. Similar major and trace element deficiencies occurred at all sites, interpreted to be a function of universal alkaline ground-water conditions.This study failed to confirm conclusively, whether European olive could be grown successfully in the semi-arid climate, typical of much of the rangelands area of Australia. As a result of the study however, successful growth in this environment is confirmed to be highly dependent on three factors. Firstly, availability of reliable irrigation waters of sufficient quality. Secondly, choice of suitable soil types. Thirdly, selection of suitable cultivars. Quality of olive oil produced from fruit appears to be influenced by local climatic factors The study also highlighted the issues of land tenure, current management attitudes and level of support within the local community as having a direct and significant impact on the trial.